Peningkatan pemahaman akhlak pergaulan dalam islam pada remaja melalui kegiatan pondok ramadhan - Nanang zamroji; umi Nahdiyah; Agus Yulianto; Redhitya wempi Ansori (Universitas Madani Indonesia, 2026)
This study aims to analyze the improvement of adolescents' understanding of Islamic social ethics through the implementation of the Ramadan Boarding School (Pondok Ramadhan) program. The activity was conducted using a socialization approach through lectures and interactive discussions involving students from SMAN Sutojayan, SMPN 2 Kademangan, and SMAN 4 Kota Blitar. The implementation was carried out in three stages: planning, implementation, and evaluation. The results indicate that the Pondok Ramadhan program significantly contributes to improving students’ understanding of Islamic moral values, particularly in social interactions. Participants demonstrated increased awareness of ethical behavior, including respect, tolerance, and responsibility in social relationships. Additionally, active participation during discussions reflects enhanced critical thinking and internalization of moral values. The program also promotes positive behavioral changes and strengthens students' religious character. Therefore, the Pondok Ramadhan activity can be considered an effective model for character education and moral development among adolescents through contextual and experiential religious learning.